Distribution of the reef manta ray Mobula alfredi and the oceanic manta ray Mobula birostris in the Philippines: a collaborative effort for conservation - Joshua Rambahiniarison; Ariana Agustines; Konstantinos Alexopoulos; Gonzalo Araujo; Asia O. Armstrong; Shannon Arnold; Aldrin Barruga; Titus Cañete; Segundo Conales; Kymry Delijero; Nonie P. Enolva; Anna L. Flam; et al. (Journal of Fish Biology, 2023)
Little is known about manta ray population size, structure and connectivity in the Philippines. In collaboration with dive operators, non‐governmental organizations and authorities, sightings of manta rays were collated into a single national database. Using in‐water photographs and videos gathered through citizen science and dedicated research efforts, this study compiled sightings between 2004 and 2020, showing 22 separate sites throughout the archipelago with manta rays present. A total of 392 individual reef manta rays ( Mobula alfredi ) and 107 oceanic manta rays ( Mobula birostris ) were identified from the collected footage. Four specific sites in the provinces of Masbate and Palawan together hosted 89% of all identified individuals and accounted for 95% of sightings, highlighting these areas are key aggregation sites. This study also reports the movements of M. birostris within the Philippines, based on photo‐identification of three individuals moving 150 km between Cebu and Masbate. Despite the growing number of recreational divers in Daanbantayan and San Jacinto, an 80% decline in M. birostris sightings was observed at these sites. To ensure effective future conservation, it is recommended that efforts focus on the identification and protection of manta ray hotspots and migratory corridors, the creation of a sustainable tourism framework and, most important, the implementation of mitigation strategies to reduce fisheries interactions.

Status of Southeast Asia's marine sharks and rays - Naomi Clark‐Shen; Andrew Chin; Sirachai Arunrugstichai; Jessica Labaja; Meira Mizrahi; Benaya Simeon; Neil Hutchinson (Conservation Biology, 2023)
In Southeast Asia, elasmobranchs are particularly threatened. We synthesized knowledge from the peer‐reviewed and gray literature on elasmobranchs in the region, including their fisheries, status, trade, biology, and management. We found that 59% of assessed species are threatened with extinction and 72.5% are in decline; rays were more threatened than sharks. Research and conservation is complicated by the socioeconomic contexts of the countries, geopolitical issues in the South China Sea, and the overcapacity and multispecies nature of fisheries that incidentally capture elasmobranchs. The general paucity of data, funds, personnel, and enforcement hinders management. Reduced capacity in the general fishery sector and marine protected areas of sufficient size (for elasmobranchs and local enforcement capabilities) are among recommendations to strengthen conservation.

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Donsol: an important reproductive habitat for the world's largest fish Rhincodon typus ? - Joni A. Miranda; Natasha Yates; Ariana Agustines; Nonie P. Enolva; Jessica Labaja; Christine Legaspi; Emer McCoy; Alessandro Ponzo; Sally Snow; Gonzalo Araujo (Journal of Fish Biology, 2021)
Little is known about the reproductive ecology of the whale shark Rhincodon typus . On 15 March 2020, a free‐swimming neonate whale shark was found in the shallow, coastal waters of Donsol, Philippines. The total length of the male shark was 60 cm, falling within the species known size‐at‐birth. This is the third occurrence of neonatal whale sharks reported in the area, and coupled with the occurrence of juveniles and adults, and anecdotal mating and precopulatory behaviour reported herein, the importance of the site for this endangered species is highlighted.

Whale sharks Rhincodon typus get cleaned by the blue‐streak cleaner wrasse Labroides dimidiatus and the moon wrasse Thalassoma lunare in the Philippines - Gonzalo Araujo; Joni A. Miranda; Harriet L. Allen; Jessica Labaja; Sally Snow; Alessandro Ponzo; Christine G. Legaspi (Journal of Fish Biology, 2020)
Cleaning interactions are essential for healthy marine ecosystem communities. This study reports the first documentation of the whale shark Rhincodon typus cleaning behaviour in the Indo‐West Pacific by two wrasse species, the blue‐streak cleaner wrasse Labroides dimidiatus and the moon wrasse Thalassoma lunare in Cebu, Philippines. This study documented 36 cleaning interactions with 14 individual whale sharks. The cleaning interactions appear opportunistic rather than targeted by the sharks, unlike that observed in other species of elasmobranchs. Further work should focus on understanding the drivers of these unique cleaning interactions.

Getting the most out of citizen science for endangered species such as whale shark - Gonzalo Araujo; Abdul R. Ismail; Cat McCann; David McCann; Christine G. Legaspi; Sally Snow; Jessica Labaja; Mabel Manjaji‐Matsumoto; Alessandro Ponzo (Journal of Fish Biology, 2020)

Long-Term Photo-Identification Reveals the Population Dynamics and Strong Site Fidelity of Adult Whale Sharks to the Coastal Waters of Donsol, Philippines - Emer McCoy; Raul Burce; David David; Elson Q. Aca; Jennifer Hardy; Jessica Labaja; Sally J. Snow; Alessandro Ponzo; Gonzalo Araujo (Frontiers in Marine Science, 2018)

Life History, Growth, and Reproductive Biology of Four Mobulid Species in the Bohol Sea, Philippines - Joshua M. Rambahiniarison; Mary Jane Lamoste; Christoph A. Rohner; Ryan Murray; Sally Snow; Jessica Labaja; Gonzalo Araujo; Alessandro Ponzo (Frontiers in Marine Science, 2018)